Genome-wide association analysis identified SNPs closely linked to a gene resistant to Soil-borne wheat mosaic virus - Liu, Shubing; Yang, Xiping; Zhang, Dadong; Bai, Guihua; Chao, Shiaoman; Bockus, William W. (My University, 2014)
Soil-borne wheat mosaic virus (SBWMV) disease is a serious viral disease of winter wheat growing areas worldwide. SBWMV infection can significantly reduce grain yield up to 80%. Developing resistant wheat cultivars is the only feasible strategy to reduce the losses. In this study, wheat Infinium iSelect Beadchips with 9K wheat SNPs were used to genotype an association mapping population of 205 wheat accessions. Six new SNPs from two genes were identified to be significantly associated with the gene for SBWMV resistance on chromosome 5D. The SNPs and Xgwm469, a SSR marker that has been reported to be associated with the gene, were mapped close to the gene using F6-derived recombinant inbred lines (RILs) from the cross between a resistant parent ‘Heyne’ and a susceptible parent ‘Trego’. Two representative SNPs, wsnp_CAP11_c209_198467 and wsnp_JD_c4438_5568170, from the two linked genes in wheat were converted into KBioscience Competitive Allele-Specific Polymerase (KASP) assays and can be easily used in marker-assisted selection to improve wheat resistance to SBWMV in breeding.
Citation: Liu, S., . . . & Bockus, W. (2014). Genome-wide association analysis identified SNPs closely linked to a gene resistant to Soil-borne wheat mosaic virus. Theoretical and Applied Genetics, 127(5), 1039-1047. https//www.doi.org/10.1007/s00122-014-2277-z
Keywords: SBWMV resistance; Association mapping; Triticum aestivum; Polymyxa graminis; 9K wheat SNP chip; KASP marker; Soil-borne wheat mosaic virus